2013
DOI: 10.1371/journal.pone.0073381
|View full text |Cite
|
Sign up to set email alerts
|

Publication Pressure and Burn Out among Dutch Medical Professors: A Nationwide Survey

Abstract: BackgroundPublication of scientific research papers is important for professionals working in academic medical centres. Quantitative measures of scientific output determine status and prestige, and serve to rank universities as well as individuals. The pressure to generate maximum scientific output is high, and quantitative aspects may tend to dominate over qualitative ones. How this pressure influences professionals’ perception of science and their personal well-being is unknown.Methods and FindingsWe perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 33 publications
6
76
0
4
Order By: Relevance
“…Early-and mid-career scientists have expressed concerns that competition and publication pressures negatively affect how science is done (Anderson, Horn, et al, 2007), and academic age has been found to be negatively correlated with experienced publication pressure (Tijdink et al, 2013). This may lead established scientists to believe that early-career scientists are more likely to engage in QRPs (and thus fit the storybook image less well) than PhD students and established scientists, but studies comparing self-admitted usage of QRPs and misbehavior between scientists of different career-stages have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early-and mid-career scientists have expressed concerns that competition and publication pressures negatively affect how science is done (Anderson, Horn, et al, 2007), and academic age has been found to be negatively correlated with experienced publication pressure (Tijdink et al, 2013). This may lead established scientists to believe that early-career scientists are more likely to engage in QRPs (and thus fit the storybook image less well) than PhD students and established scientists, but studies comparing self-admitted usage of QRPs and misbehavior between scientists of different career-stages have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a meta-analysis including studies from various fields of science showed that over 14% of scientists claimed that they had witnessed serious misconduct by their peers, and that up to 72% of scientists reported to have witnessed questionable research practices (Fanelli, 2009). Third, publication pressure and competition in science are perceived as high (Tijdink et al, 2014;Tijdink, Vergouwen, & Smulders, 2013), while scientists have expressed concerns that competition "contributes to strategic game-playing in science, a decline in free and open sharing of information and methods, sabotage of others' ability to use one's work, interference with peer-review processes, deformation of relationships, and careless or questionable research conduct" (Anderson, Horn, et al, 2007). Based on these reports, one would expect scientists' belief in the storybook image of the scientist to be low compared to lay people's belief.…”
Section: "Scientists Are Human and So Sometimes Do Not Behave As Thementioning
confidence: 99%
“…This concern is understandable in a scientific scenario where researchers are pressured to increase their production of articles for publication, putting at risk the quality and validity of the results presented 33 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, clinical faculty and residents are facing increased pressure to publish [18,19], and writing a case report is a relatively quick and easy way to engage in scholarship. To meet a growing demand for venues in which to publish case reports, new peer-reviewed journals that focus-sometimes exclusively-on publishing case reports have rapidly emerged over the last several years ( Figure 1).…”
Section: Rapid Emergence Of New Case Reports Journalsmentioning
confidence: 99%